“I don't know how I'm still standing” a Bakhtinian analysis of social housing and health narratives in East London - Thompson, C; Lewis, D; Greenhalgh, T; Smith, N; Fahy, A; Cummins, S (Elsevier, 2017)
Housing is a significant determinant of health and substandard housing is a public health issue. East London has long had a shortage of social and affordable housing, worsened in recent years by a combination of stressors. In one of East London’s most deprived boroughs, Newham, changes brought about by the 2011 Localism Act and the unique demands of being the host Olympic borough in 2012 have brought considerable pressures to bear on social infrastructure. This paper examines how these pressures were experienced by local residents via their narratives of social housing and health. The data reported here are from a qualitative study comprising two waves of data collection. Narrative family interviews and go-along interviews were conducted with 40 Newham residents at wave one and 28 at wave two. A narrative analysis with a Bakhtinian interpretation was undertaken. This revealed that residents framed experiences of social housing in terms of an inherent system level ideology based on notions of need and waiting. A particularly striking feature of this ideology was the extent to which descriptions of ill health and impairment were implicated in constructions of housing need; participants directly attributed a range of health complaints to their housing predicaments, including stress, depression, cancer scares, panic attacks and loss of sleep. Understanding the contested ideology of social housing can illuminate both the dynamic processes of social exclusion and the ways in which its subjects seek to resist it.